The Effectiveness of Demonstration Method in Improving The Students Speaking Skills - Payung, Aslinda Liling; Baa, Sultan; Asriati, Asriati (State University of Makassar, 2025)
This pre-experimental research involved one class that was given special treatment. The purpose of this research is to find out how effective the demonstration method is in improving the speaking skills of students in the twelfth grade of Frater High School. This research involved Frater High School students who were in the twelfth grade. In this study, a group of students from class twelve (XII), consisting of 25 students, was randomly selected. Speaking tests before and after treatment are part of the data collection process. To compare test results, data collected from the oral speaking test was analyzed quantitatively using the IBM SPSS Version 26 program.. Using a paired sample t-test before and after the material. The analysis's findings indicate that the